Identifikasi dan Pemetaan Problem Pembelajaran Siswa Berdasarkan Aspek Kepribadian, Motivasi, dan Lingkungan Belajar Sekolah Kelas IX Mata Pelajaran IPA di SMP Negeri 1 Batujaya Karawang - Siregar, Julinda; Priharyanti, Rifani; Nurholipah; Destikasari; Irman; Hadi, Nur; Mas’udah, Hikmah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This study aims to analyze the effect of academic resilience on student engagement among Psychology students at Surabaya State University. Changes in the learning system in the digital era require students to have high adaptive skills to academic pressure, making academic resilience a crucial factor in maintaining learning engagement. The research approach used was a quantitative correlational approach, with a population of all active students in the 2025/2026 academic year. The study sample was determined using proportional stratified random sampling with a minimum of 200 respondents. The main instruments used included the Academic Resilience Scale (ARS-30) (Cassidy, 2016; adaptation by Erawati, 2024) and the Utrecht Work Engagement Scale for Students (UWES-9S) (Schaufeli et al., 2002; Carmona-Halty et al., 2019). Data analysis was performed using simple linear regression with SPSS version 26 to determine the effect of academic resilience on student engagement. The results showed that academic resilience had a positive and significant effect on student engagement. Students with high levels of academic resilience tend to demonstrate greater engagement in behavioral, emotional, and cognitive aspects during the learning process. These findings confirm that students' ability to cope with academic pressure and manage negative emotions is a protective factor against decreased learning engagement. Furthermore, descriptive analysis shows that levels of academic resilience and student engagement are in the moderate-high category, with variations based on year and gender. Theoretically, these results support Self-Determination Theory (Deci & Ryan, 2000), which states that students with high academic resilience have stronger intrinsic motivation because they are able to fulfill basic psychological needs for autonomy, competence, and social connectedness. Practically, the results of this study are expected to provide a basis for developing psychological interventions and learning strategies that support increased academic resilience and active student engagement in higher education.